Investigate of the Relationship between Thinking Styles and Classroom Management of the Teachers of Vocational Colleges - Hu, Weiguo; Ye, Zi; Chen, Chou; Chen, Wei; Li, Chan; Zhou, Haijun; Chen, Ruiyang (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background: This study investigated the relationship between thinking styles and classroom management among teachers at X (anonymous) Vocational College of China during the academic year 2021-2022. Materials and Methods: The population of the study consisted of all 442 teachers at X Vocational College. Descriptive and inferential statistical techniques, including Fisher's Z test, were employed for data analysis. Results: The findings revealed that only the legislative and judicial thinking styles significantly predicted classroom management among the teachers. Additionally, thinking style was found to be a potential predictor of classroom management style. However, the results of Fisher's Z test indicated no statistically significant difference between teachers' thinking styles and classroom management based on gender. Conclusion: The study concludes that specific thinking styles, particularly legislative and judicial, play a role in influencing classroom management. Gender does not appear to significantly affect the relationship between thinking styles and classroom management among teachers.
Keywords: Classroom Management styles; Teacher thinking; Thinking styles; Vocational College